2021
DOI: 10.1080/17512433.2021.1947796
|View full text |Cite
|
Sign up to set email alerts
|

Patient initiation and maintenance of GLP-1 RAs for treatment of obesity

Abstract: Introduction: Healthcare providers (HCPs) see many patients with obesity-related complications and are therefore well placed to help treat obesity itself. However, limited collated information exists to help HCPs with the practical use of anti-obesity medications (AOMs). We focus on the initiation and maintenance of a glucagon-like peptide-1 receptor agonist (GLP-1 RA) for weight management, liraglutide 3.0 mg. Literature search was conducted between 25-28 November 2019 on PubMed and ClinicalTrials.gov. Areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…13 With regard to safety and tolerability, GLP-1RAs have been associated with GI tract-related AEs that are more frequent during dose escalation. 14 Similarly, in this study, orforglipron-treated participants reported more GI tract-related TEAEs than those who received placebo; however, these were not serious. Most of the GI tract-related AEs in orforglipron-treated participants occurred in the first week after initial dosing, indicating that the starting dose is as important as the frequency and magnitude of escalation.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…13 With regard to safety and tolerability, GLP-1RAs have been associated with GI tract-related AEs that are more frequent during dose escalation. 14 Similarly, in this study, orforglipron-treated participants reported more GI tract-related TEAEs than those who received placebo; however, these were not serious. Most of the GI tract-related AEs in orforglipron-treated participants occurred in the first week after initial dosing, indicating that the starting dose is as important as the frequency and magnitude of escalation.…”
Section: Discussionsupporting
confidence: 49%
“…With regard to safety and tolerability, GLP‐1RAs have been associated with GI tract‐related AEs that are more frequent during dose escalation 14 . Similarly, in this study, orforglipron‐treated participants reported more GI tract‐related TEAEs than those who received placebo; however, these were not serious.…”
Section: Discussionmentioning
confidence: 48%
“…Modern studies have confirmed the positive effect of Liraglutide in treating patients who have regained weight after bariatric surgery [ 44 ]. Recent studies confirm the positive effect of Liraglutide 3.0 mg on weight loss in patients and indicate a positive effect of the drug on the metabolism of myocardial cells [ 45 ]. New findings indicate the efficacy of Liraglutide 3.0 mg subcutaneously in obese patients [ 46 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 96%
“…Aiming at the treatment of obesity, according to Zizzari et al [ 8 ], the most sold peptide drug to treat metabolic diseases is liraglutide (Victoza ® ), an analog of glucagon-like peptide (GLP-1), resistant to degradation by the gastrointestinal tract enzyme dipeptidyl peptidase 4 (DPP-4). This analog prolongs the half-life of GLP-1 and, consequently, its action [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%